2007
DOI: 10.1002/pssa.200675344
|View full text |Cite
|
Sign up to set email alerts
|

The biocompatibility microorganisms‐carbon nanostructures for applications in microbial fuel cells

Abstract: Bionanocomposites Staphylococcus aureus /carbon nanotubes were prepared and their biocompatibility with different species of carbon nanotubes (CNTs) evaluated in terms of their incorporation into a microbial fuel cell (MFC) anodic design. Multi wall carbon nanotubes (MWNTs) with various morphologies and structures, as received, and synthesized by the pyrolysis of novolac with ferrocene addition were used. MWNTs were characterized by TEM and FT‐IR spectroscopy. Optical microscopy with fluorescent quantum dots (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…[70] Chitosan-CNT bionanocomposites with a cellular structure allow colonization of Escherichia coli, to result in a promising biohybrid material for MFC applications. [71] The precedent examples justify the great importance of CNT-based biohybrids for novel uses, which make them good candidates for the further development of advanced multifunctional materials for sensing and other applications.…”
Section: Assembly Of Biological Species To Microor Nanoparticulated Smentioning
confidence: 99%
“…[70] Chitosan-CNT bionanocomposites with a cellular structure allow colonization of Escherichia coli, to result in a promising biohybrid material for MFC applications. [71] The precedent examples justify the great importance of CNT-based biohybrids for novel uses, which make them good candidates for the further development of advanced multifunctional materials for sensing and other applications.…”
Section: Assembly Of Biological Species To Microor Nanoparticulated Smentioning
confidence: 99%
“…Although CNTs were claimed to exhibit antimicrobial capability as discussed previously, the cytotoxicity behavior decreases after their modification and functionalization (Sayes et al, 2006). Investigation of the biocompatibility of Staphylococcus aureus with CNTs by Morozan et al (2007) showed rapid microorganism growth in CNTmodified cell culture media. This points to the potential of reducing the loss of power generation if applied to MFC anodic design.…”
Section: Carbon Nanotubes In Biotechnologymentioning
confidence: 86%
“…However, the technology is not feasible practically, primarily due to low performance and lack of technical maturity. Intensive work has been focused on employing and modifying CNTs as electrodes to increase power production in MFC because of their high conductivity and large surface area (Morozan et al, 2007;Qiao et al, 2007;Sharma et al, 2008;Tsai et al, 2009). Tsai et al (2009) prepared a new type of electrode architecture by coating CNTs onto a carbon cloth to form a highly conductive electrode with high specific surface-area in MFC.…”
Section: Carbon Nanotubes In Biotechnologymentioning
confidence: 99%
“…In such devices, the CNTs constitute the carbon electrodes where a colony of microorganisms is incorporated, and the whole system converts the microbial reducing power to electrical energy. In a recent work, a carbonaceous material derived from MWNTs was used as a biocompatible support for the growth of Staphylococcus aureus, a Gram-positive bacterium, and the resulting bio-hybrid material was proposed for further application in MFCs [186]. In order to increase the specific surface area of the carbon electrode, the MWNTs have been processed as a macroporus scaffold by means of ISISA (ice segregation induced self-assembly) process, with the help of chitosan to homogeneously disperse the CNTs [187].…”
Section: Bionanocomposites For Sensor Devices and Other Applicationsmentioning
confidence: 99%